FEMALE RADICALISM: METHODS OF PREVENTION - AITZHANOVA, Dinara (CENTRAL ASIA AND THE CAUCASUS, 2019)
Global migrations in the final years of the 20th century have transformed large countries into multicultural and multi-confessional societies. In the past, a single confession dominated in most states; however, this phenomenon is gradually disappearing. In these diverse societies, the emergence and popularity of various religious trends have gained special significance. Today, tolerant and peace-loving religious movements compete with radical ideologies for followers. Under the guise of the constitutional principle of freedom of conscience, radical and extremist ideas are spreading across states and among both genders.The article discusses the feminization of extremism in Central Asia and other regions, examining the conditions and factors that have led to a notable increase in the number of radicalized women. It assesses the role of society and its traditional values, sham religious organizations, and various NGOs in the spread of radical extremist ideas. Additionally, it explores the experiences of different countries in preventing religious extremism and radical ideologies, as well as the de-radicalization of women.Particular attention is given to the problem of female extremism in Kazakhstan, focusing on the factors that contribute to its rise within the context of the republic's traditional lifestyle. The article also discusses prevention and rehabilitation efforts and the roles of the state, NGOs, and other public organizations in this process.